Ekvin virtuell anatomi : ljuset i tunneln - Johansson, Annika (SLU/Dept. of Clinical Sciences (until 231231), 2011)
Summary: The Clinical Training Center at the Swedish University of Agricultural Sciences in Uppsala uses new methods for educating and training veterinary students. Among these methods are computer programs. The aim of this study was to create an interactive application based on data from horses CT-scanned at the Center for Medical Image and Visualization at Linköping University Hospital. The purpose of this application is for veterinary students to be able to use multidimensional visualization to study equine anatomy. The resulting application named "EQUINE VIRTUAL ANATOMY - Flash in the Tunnel" consists of data from six heads, one left foreleg and a wooden dalahorse. Interactive options give the user the ability to shift between different color variations and 3D projections around and through the horses head and leg. This application introduces a new way to the study of equine anatomy.